2022
DOI: 10.1038/s42003-022-03468-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids promote the effect of environmental signals on the gut microbiome and metabolome in mice

Abstract: Gut microorganisms and the products of their metabolism thoroughly affect host brain development, function and behavior. Since alterations of brain plasticity and cognition have been demonstrated upon motor, sensorial and social enrichment of the housing conditions, we hypothesized that gut microbiota and metabolome could be altered by environmental stimuli, providing part of the missing link among environmental signals and brain effects. In this preliminary study, metagenomic and metabolomic analyses of mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…SCSFAs activate many types of neurons in the enteric nervous system modulating neurotransmitter release such as serotonin, gamma-aminobutyric acid (GABA), and acetylcholine, which have all been implicated in the regulation of mood and behavior [ 49 ]. A recent study showed that supplementation with a mixture of SCFAs increased microbiota diversification and improved cognition and stress in healthy human participants [ 50 ]. SCFAs can also influence the production of brain-derived neurotrophic factor (BDNF), a neurotrophin that is involved in neuronal growth and plasticity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCSFAs activate many types of neurons in the enteric nervous system modulating neurotransmitter release such as serotonin, gamma-aminobutyric acid (GABA), and acetylcholine, which have all been implicated in the regulation of mood and behavior [ 49 ]. A recent study showed that supplementation with a mixture of SCFAs increased microbiota diversification and improved cognition and stress in healthy human participants [ 50 ]. SCFAs can also influence the production of brain-derived neurotrophic factor (BDNF), a neurotrophin that is involved in neuronal growth and plasticity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings extend these previously observed neurotrophic effects by identifying an increase in hippocampal BDNF in response to a HFD that is positively correlated with increasing acetic acid. Indeed, administration of acetate in mice was recently observed to promote brain plasticity and increase BDNF mRNA expression in the hippocampus ( Marrocco et al, 2022 ) underscoring the potential mechanistic role for serum acetic acid elevations to enhance brain plasticity and function.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds regulate numerous metabolic pathways both in the intestine and at a distant level, that is, at the level of the liver, adipose tissue, muscles, and brain. It is in fact well known that SCFAs contribute to numerous physiological effects, ranging from modulation of energy homeostasis, glucose/lipid metabolism, inflammation and even immunity and cancer (Pascale et al ., 2018; Silva et al ., 2020; Marrocco et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%